2018
DOI: 10.1021/acs.analchem.8b04070
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecularly Multicolor DNA Decoding Using an Indicator Competition Assay

Abstract: Scheme 1. ICA Rationale (A) Proposed in This Work and the Previously Developed Rationales of IDA (B), ABA (C), and DBA (D) a a For (D), with analyte also serving as indicator. I: indicator; A: analyte. Letter pubs.acs.org/ac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Palmatine (PAL) is a clinically important natural isoquinoline alkaloid that has attracted much attention due to various biochemical and pharmacological effects, PAL is also fluorescent guest that can interact with water‐soluble Q[7], and various research groups have employed the PAL@Q[7] inclusion complex as a fluorescence probe to determine organic compounds, including drugs,‐ amino acids, pesticide, and for use in biological monitoring and preservatives . Recent research demonstrated that the PAL@Q[7] inclusion complex can be used for supramolecular multicolor DNA decoding . However, inclusion complexes between PAL and Q[n]s other than Q[7] have not yet been reported.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Palmatine (PAL) is a clinically important natural isoquinoline alkaloid that has attracted much attention due to various biochemical and pharmacological effects, PAL is also fluorescent guest that can interact with water‐soluble Q[7], and various research groups have employed the PAL@Q[7] inclusion complex as a fluorescence probe to determine organic compounds, including drugs,‐ amino acids, pesticide, and for use in biological monitoring and preservatives . Recent research demonstrated that the PAL@Q[7] inclusion complex can be used for supramolecular multicolor DNA decoding . However, inclusion complexes between PAL and Q[n]s other than Q[7] have not yet been reported.…”
Section: Introductionmentioning
confidence: 74%
“…Although the interaction between Q[7] and PAL are well characterised, interaction between Q[8] and PAL has not been demonstrated, presumably due to the limited water solubility of Q[8]. However, we found that in neutral water, interaction between Q[8] and PAL not only improved the water‐solubility of Q[8], but was also accompanied by fluorescence enhancement of PAL.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 In 2018, Y. Shao and co-workers described a supramolecular multicolor DNA sensor for the selective recognition of abasic DNA sites based on the ICA concept with CB [7]. 55 Two natural alkaloids, namely coptisine (21) and palmatine (22) have been used as fluorescent indicators for AP DNA sites (Scheme 3). Both alkaloids form 1 : 1 inclusion complexes with CB [7] that is accompanied by pronounced increase of their fluorescence.…”
Section: Supramolecular Dna Sensingmentioning
confidence: 99%
“…The strategy efficiently enhanced the sensitivity of the split aptamer-based sensor. Moreover, the strategy could be extended to multiplexed analysis based on the diversity of available responsive dye-macrocycle systems 76,77.…”
Section: Dsc-based Sensors For Bioanalysismentioning
confidence: 99%